Influence of heat treatment combined with cryogenic treatment on contact fatigue properties of Cr12Mo1V1 steel members - Yuhong Liu; Qingshan Jiang; Jiashun Gao; Zhilong Xu; Shiqi Chen; Yongqing Lai; Weiqing Wang; Jianchun Weng; Bo Li; Liting Ye; Zhilong Xu Mailbox (Scientific Reports)
Abstract Cold work die steel Cr12Mo1V1 is often used in metal plastic forming processing such as spinning, stamping, quenching, and tempering. It has a high hardness but still contains a lot of unstable residual austenite, which is prone to phase change in the service process to cause stress concentration, seriously affecting the contact fatigue performance of components. This paper studied the effects of different heat treatment processes on microhardness, residual stress, residual austenite content, and contact fatigue properties of Cr12Mo1V1 steel members by combining the cryogenic process with low-temperature and high-temperature tempering. The results show that the residual austenite content of the components can be reduced from 21.3 to 2.6%, and the contact fatigue life of the components can be increased by 1.89 times compared with the low-temperature tempering method.